The distribution of organochlorine pesticides in surface soils from Mongolia - Elena Mamontova (Chemical Bulletin of Kazakh National University, 2015)
Organochlorine pesticides (OCPs) were measured in fifty-nine soil samples in urban and background and rural areas throughout Mongolia to fill up the gap in data set of OCPs in soil in Central Asia. The median of α-HCH+γ-HCHs, p,p`-DDT+p,p`-DDE+p,p`-DDD and HCB comes to 0.02, 0.16 and 0.02 ng/g dry weight respectively. OCPs levels in soils from rural and background regions of Mongolia are comparable or lower than those obtained in soil of remote and mountain areas of the world. The influence of some factors including land use, soil organic carbon, natural zones and latitude on OCP distribution in surface soils in Mongolia was found. It is associated with the extensive development of agriculture and stock-breeding in central and northern parts of Mongolia.